Research trends in aerobic gymnastics in school settings: A bibliometric analysis - Jusuf, Jeane Betty Kurnia; Santoso, Januar Abdilah; Julianur, Julianur; Mahardhika, Nanda Alfian (Psychology, Evaluation, and Technology in Educational Research, 2024)
This study presents a bibliometric analysis of 5335 articles published between 2013 and 2023, aimed at exploring the research landscape of aerobic gymnastics in school settings. The study aims to identify key research categories, publication trends, and geographic distribution of publications. A bibliometric analysis was conducted using data from the Dimensions database, focusing on peer-reviewed journal articles, conference papers, and scholarly outputs related to aerobic gymnastics in school-based physical education. The analysis reveals a multidisciplinary approach, with key research categories including education, health sciences, and public health. Publication trends indicate a significant increase in publications, particularly during the COVID-19 pandemic, demonstrating a growing interest in aerobic gymnastics as a flexible physical activity adaptable to various contexts, including remote learning. The United States, the United Kingdom, and Australia lead in publication productivity, while countries like Indonesia exhibit lower productivity, suggesting a need for increased research efforts and collaborations. The sources with the highest number of citations offer insights into the relationship between physical activity and health outcomes in relation to aerobic gymnastics. An analysis of co-authorship highlights the key researchers and collaborations that have made significant contributions to the field. This study emphasizes the importance of ongoing research and collaboration to gain a better understanding of the benefits and challenges of implementing aerobic gymnastics programs in schools. Suggestions for future research include longitudinal, comparative, intervention, and qualitative studies to enhance our understanding of the impact of aerobic gymnastics on education, health, and society.